PENGARUH ROE, EPS, DAN DER TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2020–2023 - Desmita, Devira Patria; Purwaningrum, Endang; Mirati, R Elly (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
This study aims to analyze the effect of Return on Equity (ROE), Earnings per Share (EPS), and Debt to Equity Ratio (DER) on stock returns in agricultural sector companies during the 2020–2023 period. The data used in this research are annual data obtained from the official website of the Indonesia Stock Exchange. The analysis technique used is panel data regression with a 5 percent level of significance. The results of the partial test show that ROE and DER have a significant negative effect on stock returns, while EPS does not have a significant effect. Meanwhile, the simultaneous test shows that ROE, EPS, and DER together have a significant effect on stock returns in agricultural sector companies.